(untitled) (Scientia Agricola, 2015)
Despite the importance of traditional varieties of tomato (Solanum lycopersicum L.) as sources of variation in breeding programs and varieties targeted to high-price quality markets that value their exceptional organoleptic quality, little is known regarding the structure of these materials at the morphological level. In this study, a collection of 166 populations (137 of them during two years) of traditional varieties of tomato from the east coast of Spain has been characterized using 41 descriptors. The characterization revealed a considerable variation. The segregation observed in several populations (28 %) suggests that apart from the configuration as population varieties, the high variation present in these landraces may be partially due to possible seed mixing and spontaneous cross-pollination. Only nine fruit descriptors were required to represent the variation present in the collection analyzed. It seems that after spontaneous cross-pollinations, farmers applied strong selection to a small number of traits, though even in these traits a high level of variation is maintained. The variation observed may hinder clear recognition by the consumer, an attribute required for the consolidation of quality markets. Additionally, a registry of these materials as conservation varieties would be complicated considering the actual levels of variation. Therefore, a varietal depuration would be interesting in order to promotein situ conservation of these resources. Finally, the high levels of variation in the intra-varietal scale may justify the collection and maintenance of more populations of the same variety as the risk of conserving duplicates would not be so high.